Introducing a two‐dimensional graph of docking score difference vs. similarity of ligand‐receptor interactions - Mohammad Rizki Fadhil Pratama; Hadi Poerwono; Siswandono Siswodihardjo (Universitas Gadjah Mada, 2021)
Observation of molecular docking results was generally performed by analyzing the docking score and the interacting amino acid residues separately either in tables or graphs. Sometimes it was not easy to rank the tested ligands’ docking results, especially if there were many ligands. This study aims to introduce a new way to analyze docking results with a two‐dimensional graph between the difference in docking score and the similarity of ligand‐receptor interactions. Molecular docking was performed with one reference ligand and several test ligands. The docking score difference was obtained between the test and the reference ligands as the graph’s x‐axis. Meanwhile, the y‐axis contains the similarity of ligand‐receptor interactions, obtained from the ratio of amino acid residues and the types of interactions between the test and reference ligands. Docking result analysis was more straightforward because two critical parameters were presented in one graph. This graph could be used to support the analysis of the docking results.